Simultaneous detection of the protozoan parasites Toxoplasma, Cryptosporidium and Giardia in food matrices and their persistence on basil leaves. (August 2016) - Hohweyer, Jeanne; Cazeaux, Catherine; Travaillé, Emmanuelle; Languet, Emilie; Dumètre, Aurélien; Aubert, Dominique; Terryn, Christine; Dubey, Jitender P.; Azas, Nadine; Houssin, Maryline; Loïc, Favennec; Villena, Isabelle; et al.
Abstract: Toxoplasma gondii, Cryptosporidium spp. and Giardia intestinalis are emerging pathogen parasites in the food domain. However, without standardized methods for their detection in food matrices, parasitic foodborne outbreaks remain neglected. In this study, a new immunomagnetic separation assay (IMS Toxo) targeting the oocyst's wall of T. gondii was developed using a specific purified monoclonal antibody. Performance of this IMS Toxo coupled to microscopic and qPCR analyses was evaluated in terms of limit of detection (LOD) and recovery rate (RR) on: i) simple matrix (LOD = 5 oocysts; RR between 5 and 56%); ii) raspberries and basil (LOD = 33 oocysts/g; RR between 0.2 and 35%). Finally, to simultaneously extract the three protozoa from these food matrices, T. gondii oocysts were directly concentrated (without IMS Toxo) from the supernatant of the IMS of Cryptosporidium and Giardia (oo)cysts. This strategy associated to qPCR detection led to LOD <1 to 3 (oo)cysts/g and RR between 2 and 35%. This procedure was coupled to RT-qPCR analyses and showed that the three protozoa persisted on the leaves of basil and remained viable following storage at 4 °C for 8 days. These data strengthen the need to consider these protozoa in food safety. Highlights: A novel direct IMS capture of T. gondii oocysts is presented. A new method to extract T. gondii, C. parvum, G. duodenalis (oo)cysts from food is proposed. Recovery rates (2–35%) and limits of detection (≤3 (oo)cysts/g) are defined by qPCR. Protozoa remain viable on the surface of basil for 8 days at 4 °C.